Intelligent cloud based monitoring system of electricity demand of fused magnesium furnace process. (2017) - Yang, Jie; Lu, Shaowen; Wang, Liangyong; Xu, Quan
We introduce a monitoring system of electricity demand of fused magnesium furnace (FMF) process. Fused magnesia is commonly used in producing fire-resistant materials. The manufacturing process of fused magnesia with electric arc melting furnace is highly energy intensive. The main purpose of monitoring the electricity power demand is to avoid the demand spikes which may break the limit imposed by local grid operators. We present a data-driven approach to forecast the event of demand threshold breakout. The monitoring system proposed in this paper employs cloud computing technology to support remote and mobile monitoring. Also, a three dimensional visual simulation of the manufacturing scene is provided as an auxiliary monitoring function.